Morphologic Characteristics of the Submandibular Salivary Gland of the Collared Peccary (Tayassu Tajacu) - Reginato, Gabriela de Souza; Bolina, Cristina de Sousa; Oliveira, Moacir Franco; Almeida, Sonia Regina Yokomizo; Watanabe, Ii-sei; Ciena, Adriano Polican (Journal of Morphological Sciences, 2018)
Introduction Most salivary glands is located on the inside and around the oral cavity, and are divided into major and minor salivary glands. The aim of the present study was to describe the structural and ultrastructural morphological characteristics of the lingual tissue of the submandibular glands of the collared peccary (Tayassu tajacu).Materials and Methods The submandibular glands (n = 10) of adult male collared peccaries (T. tajacu) were used for histological and ultrastructural analysis. The techniques used were light microscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM).Results The submandibular salivary glands of the collared peccary (T. tajacu) showed a capsule formed by a connective tissue containing the acinus and duct cells. Histologically, the nuclei located at the basal region of the cells was observed. The light polarized microscopy clearly showed the presence of type I and type III collagen. In the SEM image, the submandibular salivary gland revealed a round aspect separated in several lobules with bundles of collagen fibers. The vibratome sections showed the groupings of acinar cells, with intermingled secretory ducts containing vessels of different diameters. The secretory granules were noted in the apical portion of the acinar and ductal cells. The thick bundles of collagen fibers formed a glandular capsule and were identified around of the acinar and ductal cells in three-dimensional SEM images. The TEM images showed a number of secretory granules, especially in the apical region of the cytoplasm of the acinar cells and in the basal portion of the nuclei. The granular endoplasmic reticulum area, the euchromatic nuclei and the cytoplasmic projections may be seen. Mucous acinar cells separated by fine collagen fibers were also observed.Conclusion The morphological characteristics of the submandibular gland of the collared peccary is similar to that of other mammals with the same eating habits and habitat.
Keywords: submandibular salivary gland; acinar cells; collared peccary; TEM; SEM